Degradation of Platinum-Cobalt Alloy PEMFC Cathode Catalysts in Catalyst-Ionomer Inks. Issue 4 (12th April 2021) - Myers, Deborah J.; Kropf, A. Jeremy; Wegener, Evan C.; Mistry, Hemma; Kariuki, Nancy; Park, Jaehyung
Abstract : In this paper we report on studies of the effects of catalyst-ionomer ink composition: ionomer equivalent weight (EW), ink solvent, and ink mixing on a commercial PtCo alloy PEMFC cathode catalyst. X-ray absorption spectroscopy (XAS) and wide-angle X-ray scattering (WAXS) are utilized to determine catalyst atomic structure, catalyst crystallite composition, and extent of loss of Co into the ionomer-solvent phase. Three different n-propanol to water weight ratios (7:3, 5:5, and 3:7) and two different ionomers (3 M 800 EW and Nafion 1000 EW) were studied. Cobalt loss from the PtCo particles was found to increase with increasing water content in the inks and to be more extensive for the 800 EW ionomer inks, causing loss of contraction of the PtCo lattice and formation of a Pt shell-PtCo alloy core intraparticle structure.